The retraction of the protoplast during PCD is an active, and interruptible, calcium-flux driven process. (July 2017) - Kacprzyk, Joanna; Brogan, Niall P.; Daly, Cara T.; Doyle, Siamsa M.; Diamond, Mark; Molony, Elizabeth M.; McCabe, Paul F.
Highlights: Protoplast shrinkage is an active element of plant programmed cell death (PCD). The mechanism depends on calcium flux signalling and mitochondrial function. Protoplast shrinkage can precede loss of plasma membrane integrity. Programmed cell death can be delayed after protoplast shrinkage has occurred. Protoplast shrinkage is a valid and specific reporter of plant PCD. Abstract: The protoplast retracts during apoptosis-like programmed cell death (AL-PCD) and, if this retraction is an active component of AL-PCD, it should be used as a defining feature for this type of programmed cell death. We used an array of pharmacological and genetic tools to test if the rates of protoplast retraction in cells undergoing AL-PCD can be modulated. Disturbing calcium flux signalling, ATP synthesis and mitochondrial permeability transition all inhibited protoplast retraction and often also the execution of the death programme. Protoplast retraction can precede loss of plasma membrane integrity and cell death can be interrupted after the protoplast retraction had already occurred. Blocking calcium influx inhibited the protoplast retraction, reduced DNA fragmentation and delayed death induced by AL-PCD associated stresses. At higher levels of stress, where cell death occurs without protoplast retraction, blocking calcium flux had no effect on the death process. The results therefore strongly suggest that retraction of the protoplast is an active biological process dependent on an early Ca 2+ -mediated trigger rather than cellular disintegration due to plasma membrane damage. Therefore this morphologically distinct cell type is a quantifiable feature, and consequently, reporter of AL-PCD.